TRANSFEKSI DNA KE DALAM MITOKONDRIA SEL BETA PANKREAS TIKUS DAN SEL PRIMER MYOBLAST MANUSIA: LANGKAH MENUJU REKAYASA DNA MITOKONDRIA DAN TERAPI GEN - Lyrawati, Diana (Fakultas Kedokteran Universitas Brawijaya, 2004)
The delivery of an exogenous or modified DNA into the mitochondria of mammalian cells has been proposed as an alternative way to prevent or modify mitochondrial genetic defect. In this study, a lipofection method was developed to transfer exogenous DNA into mitochondria of BRIN BD11 cells, a rat beta pancreas cell line, and human myoblast primary cells. An artificial mini-mitochondrial genome carrying a reporter gene encodes for a mitochondrial green fluorescent protein (mtGFP) was usedto track the fate of the exogenous DNA following its transfection into cellular mitochondria. Epifluorescence microscopic observation was carried out to detect the green fluorescence resulted from the GFPexpression. Immunohistochemical assays were also performed to validate and confirm the GFP expression. Collectively, the results indicate that the exogenous DNA pmtGFP could be delivered into the mitochondrial compartment and was functional withinthe mitochondria of BRIN BD11 and human myoblast cells. Such achievement is a significant progress as both the artificial DNA construct and the mitochondrial transfection method could serve as a model to study the dynamic of mutant mtDNA as well as to provide a basis for the development of gene therapy for human mitochondrial diseases. Key words: DQAsome, pmtGFP, beta pancreas cell line, human myoblast primary cells